2022
DOI: 10.1002/cncy.22589
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular profiling of pancreatic ductal adenocarcinoma in FNA, biopsy, and resection specimens

Abstract: BACKGROUND Molecular testing to identify molecular alterations in pancreatic ductal adenocarcinoma (PDAC) has been increasingly requested because of potential therapeutic implications. In this study, we compared the performance of PDAC fine‐needle aspiration (FNA), fine‐needle biopsy (FNB), and resection specimens for comprehensive molecular analysis. METHODS A next‐generation sequencing–based Oncomine Comprehensive Assay (OCA) was used to analyze molecular alterations in FNA, FNB, or resection specimens. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In comparison to fine-needle biopsy (FNB) samples, studies have demonstrated similar success rates for comprehensive molecular analysis using FNA and FNB specimens of pancreatic adenocarcinoma, with complete concordance between the histologic sample and the corresponding cytologic material in almost 90% of cases [11,14]. In a study by Gan et al (2022) [15], CBs were presumed to represent samples obtained from EUS-FNB and yield optimal material for targeted NGS in PDACs, similar to cytological smears.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to fine-needle biopsy (FNB) samples, studies have demonstrated similar success rates for comprehensive molecular analysis using FNA and FNB specimens of pancreatic adenocarcinoma, with complete concordance between the histologic sample and the corresponding cytologic material in almost 90% of cases [11,14]. In a study by Gan et al (2022) [15], CBs were presumed to represent samples obtained from EUS-FNB and yield optimal material for targeted NGS in PDACs, similar to cytological smears.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] KRAS mutation in cystic fluid have relatively high sensitivity and specificity for IPMNs, 29,30 which is also the most common mutation (90%) identified in pancreatic ductal adenocarcinoma. 31 However, a small portion of mucinous cysts can have a wild-type KRAS. Thus, the specimen with a negative KRAS mutation cannot reliably be classified as a nonmucinous cyst; a diagnosis of SCA based on a negative KRAS mutation would be far from reach.…”
Section: Discussionmentioning
confidence: 99%
“…Previous whole exome sequencing studies have identified a specific mutation profile for pancreatic cystic lesions including VHL in SCA, CTNNB1 in solid pseudopapillary neoplasm, and KRAS in MCN and IPMN 26–28 . KRAS mutation in cystic fluid have relatively high sensitivity and specificity for IPMNs, 29,30 which is also the most common mutation (90%) identified in pancreatic ductal adenocarcinoma 31 . However, a small portion of mucinous cysts can have a wild‐type KRAS .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular profiling of tissue collected by fine-needle biopsy (FNB)-to assess these mutations-is less applicable for surveillance purposes, as it is invasive, relies on a visible mass, and is expected to obtain information from a single clone. Additionally, collection during endoscopic ultrasound (EUS) has been challenging due to low tumor cellularity and limited yield of tissue [4,5]. To date, for PC, carbohydrate antigen 19.9 (CA19.9) is the only serum marker implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%